Major Maternal Dietary Patterns during Early Pregnancy and Their Association with Neonatal Anthropometric Measurement. (31st May 2018) - Hajianfar, Hossein; Esmaillzadeh, Ahmad; Feizi, Awat; Shahshahan, Zahra; Azadbakht, Leila
Abstract : Background. Anthropometric measurements of newborn infant are widely assessed as determinants of maternal nutrition. Although earlier studies have mostly examined the effects of particular nutrients or foods during gestational period on neonatal anthropometric measurements, there are few studies regarding the association of dietary patterns and mentioned measurements. So, the purpose of the current study was to investigate the association between major maternal dietary patterns and neonatal anthropometric measurements including body weight, head circumference, and height. Methods. The current prospective observational study is based on the data collected from 812 pregnant women. Dietary data was collected using a validated semiquantitative food frequency questionnaire. Results. Three identified major dietary patterns according to the results obtained from the factor loading matrix were (i) "western dietary pattern"; (ii) "traditional dietary pattern"; (iii) "healthy dietary pattern". Overall, this study demonstrated a positive significant association between high adherences to western dietary pattern and chance of having low birth weight infant. However, such associations were not seen in women taking healthy and traditional dietary patterns. Conclusion. We found that healthier maternal dietary patterns during early pregnancy might be associated with lower risk of low birth weight. Further studies are required to confirm these findings.